Isolation and Evaluation of Tamarind Seed Polysaccharide as a Natural Suspending Agent - DEVESWARAN, R (International Journal of Pharmaceutical & Biological Archive, 2010)
The Tamarind seed polysaccharide (TSP) possesses properties like high viscosity, broad pH tolerance, no carcinogenicity, mucoadhesive nature, and biocompatibility. Since suspensions are thermodynamically unstable, it requires a suspending agent which reduces the rate of settling and permits easy redispersion of any settled particulate matter. So an attempt was made to use this polysaccharide as suspending agent in the formulation of Nimesulide suspension. The formulations were prepared and compared with the marketed product. All the formulations were redispersed uniformly without any deposits. The average size of the particles in the suspension was found to be 35.4 Âµm and the minimum and maximum particle size were 17.3 and 70.3 Âµm respectively. The drug content of all the formulations was in the range of 95-98.3%. The rheological study of the formulation F3 indicated that as the RPM increases the viscosity decreases, confirming the shear thinning nature of the suspension. The suspension was found to be stable during the entire period of study. Hence the present work confirms that the isolated TSP powder can be used as an effective suspending agent. But the feasibility of isolation of TSP powder in large scale needs to be studied in future.